A High‐Rate Electrode with Grotthuss Topochemistry for Membrane‐Free Decoupled Acid Water Electrolysis (Adv. Energy Mater. 40/2021). Issue 40 (27th October 2021) - Liang, Shuaika; Jiang, Miaomiao; Luo, Hongxia; Ma, Yuanyuan; Yang, Jianping
Abstract : Decoupled Water Electrolysis In article number 2102057, Yuanyuan Ma, Jianping Yang and co‐workers introduce a low‐cost and high‐rate electrode with Grotthuss topochemistry as a solid‐state redox mediator to decouple the acid water electrolysis for hydrogen production without the use of membrane. This decoupled water electrolysis system facilitates the utilization of renewable energies for high‐purity hydrogen production at different spaces and times.